Município de Assis Chateaubriand: uso da terra, paisagem e imagens do rural - Bernardo, Luciana Virgínia Mario (2020)
From the 1950s onwards, Brazil was encouraged to modify its agricultural production process by inserting the use of rural technologies. This measure has resulted in the process of restructuring the food production structure over the years and has also altered the population configuration, as most people now reside in the urban area. Thus, the present thesis was directed to the municipality of Assis Chateaubriand, located in the western region of Paraná, which has in its records the implementation of this process. The option to carry out the investigation in this location was motivated by the transformations in the use of the local land, mainly those that occurred in the rural area and that must again occur in view of the implantation of an agro-industrial company for the slaughter of pigs. The general objective established was to analyze the transformations of land use and landscape in the municipality of analysis and its reflexes in its productive structure. The approach used involved mixed methods, with an applied nature. The qualitative method was useful, in particular, for the analysis of images, while the quantitative was required in the descriptive and inferential analyzes, as specified in each stage of the research. The results identified indicate that the municipality has shown changes in its productive, land and population structure and that there has been an impoverishment of the diversity of the rural landscape, over the years, due to this agricultural production, which is predominant in the municipality. The image of young people about the local countryside is a counterpoint between the traditional characteristics of producers and changes in needs related to the current production process. Most young people still do not perceive themselves as a necessary element for the continuity of rural property. With regard to the perception of the general population, about the locality, the municipality needs to advance in relation to land use and the environment, today. And the implantation of a local swine agroindustrialization can bring positive and negative changes, however the expectations of changes are different according to the characteristics of the respondents.